High photosynthetic thermal tolerance in the Mediterranean halophyte Limoniastrum monopetalum - Figueroa-Luque, E; Figueroa, M E; Castillo, J M; Cires, A DE; Álvarez, R; Cambrollé, J; Gallego-Tévar, B (Photosynthetica, 2024)
The general increase in temperature, together with sudden episodes of extreme temperatures, are increasingly impacting plant species in the present climate change scenario. Limoniastrum monopetalum is a halophyte from the Mediterranean Basin, exposed to broad daily and seasonal changes in temperature and extreme high temperatures. We studied the photosynthetic responses (chlorophyll fluorescence dynamics and gas exchange) of L. monopetalum leaves exposed to temperatures from -7.5°C to +57.5°C under darkness in controlled laboratory conditions. L. monopetalum presented its optimum temperature for photosynthesis around +30°C. The photosynthetic apparatus of L. monopetalum exhibited permanent damages at > +40.0°C. L. monopetalum tolerated, without permanent damages, temperatures as low as -7.5°C in darkness. L. monopetalum appears as a plant species very well adapted to the seasonality of the Mediterranean climate, which may work as a pre-adaptation to stand more extreme temperatures in the actual context of accelerating climate change.
Keywords: chlorophyll fluorescence; heat wave; gas exchange; climate change; Mediterranean climate; stressor